PHARMACOKINETICS OF KETOPROFEN IN HEALTHY DONKEYS IN PAKISTAN - M. N. Anwer; M. A. Rasheed; M. Ashraf (Journal of Animal and Plant Sciences, 2012)
Ketoprofen is a non-steroidal anti-Inflammatory drug. This drug was reported as a safe alternate for diclofenac which was banned for veterinary use in Pakistan. The present study was designed to access pharmacokinetics of ketoprofen after intravenous administration in eight Healthy donkeys. Donkeys were administered through jugular vein, an intravenous dosage of ketoprofen @3.0 mg/kg body weight. Heparinized Vacutainer were used to collect blood samples (3-5 ml) before and then up to 24 hours post – medication. Plasma Ketoprofen concentrations were measured by HPLC. The data obtained the mean (+SEM) pharmacokinetic parameters of ketoprofen were, AUC (Area under the curve) = 17.02±2.61 g.h/ml, Cl (clearance) = 0.21±0.02l/h/kg, VDss (Steady state volume of distribution) = 0.47±0.04 l/kg, t1/2 (half life) = 2.2± 0.17h, and MRT (Mean Residence Time) = 2.44±0.17 hrs. The short elimination half-life and MRT were observed in donkeys when compared with horses, dogs, rats and human. The small value of AUC of Ketoprofen observed in donkeys. The lower value of Vd may be due to high protein binding of Ketoprofen which limit their ability to reach extra vascular compartments. The low plasma clearance leads to suggestion that use of Ketoprofen in donkey might be beneficial.
Keywords: Ketoprofen; Pharmacokinetics; Intravenous administration; donkeys.